Animal models of rheumatoid arthritis‐associated interstitial lung disease - Xiong, Li (Immun Inflamm Dis, 2020)
BACKGROUND: Rheumatoid arthritis‐associated interstitial lung disease (RA‐ILD) is an irreversible pathologic condition of unknown cause, commonly involving the joint and the lung with variable amounts of fibrotic change. In contrast to rheumatoid arthritis or other chronic interstitial lung diseases such as interstitial pulmonary fibrosis, there is so far no extensively accepted or implemented animal model for this disease. AIMS: To provide guidance for those who are investigating the pathogenesis of RA‐ILD with animal models. MATERIALS AND METHODS: An analysis of papers from PubMed during 1978‐2020. RESULTS: We outline the present status quo for animal models of RA‐ILD about their modeling methods and pathogenesis, compare their pros and cons with respect to their ability to mimic the clinical and histological features of human disease and discuss their applicability for future research. DISCUSSION: There is no doubt that these animal models do provide valuable information relating to the pathogenesis of RA‐ILD and the development of effective therapeutic drugs. Nevertheless, these animal models can not entirely recapitulate clinical pathology and have some limitations in experimental research application. Therefore, it should be emphasized that we should improve and explore animal models in more accordance with the pathogenesis and clinical characteristics of human RA‐ILD. CONCLUSION: These established animal models of the disease can significantly progress our understanding of the etiology of RA‐ILD, the fundamental mechanisms of its pathogenesis and the identification of new bio‐markers, and can contribute to the development and implementation of novel treatment strategies.